The Routledge handbook of language and professional communication - Bhatia, V. K. (Vijay Kumar) 1942-; Bremner, Stephen (Routledge handbooks in applied linguistics, 2014)
"The Routledge Handbook of Language and Professional Communication provides a timely overview of the field of professional communication with a clear focus on language. Encompassing a wide range of approaches, the Handbook presents an intergrated approach to professional communication, covers the development of the field and looks to possible future directions. With cutting-edge contributions from leading international researchers and interviews with professionals from the fields studied, the Handbook is a vital resource for advanced undergraduates, postgraduates and researchers in applied linguistics and professional communication"--Provided by publisher.